Ryzyko w działalności gospodarczej - Gładysz, Monika (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2006)
A risk always accompanies an economic activity. In the paper research of risk were presented. There is a tradeoff between risk and rate of return. Higher risk accompany higher rate of return. The prospect theory of Kahneman and Tversky was also presented and used to explain certain market situations